1980
DOI: 10.1093/bja/52.1.61
|View full text |Cite
|
Sign up to set email alerts
|

The Anaesthetic Machine-a Study of Function and Design

Abstract: A study of the time and motion of the anaesthetists' routine activities was made using conventional equipment. Films of manual and visual movements were studied in detail and the expectations of certain consultant anaesthetists regarding apparatus were recorded. Models of apparatus were used to test their acceptability. A modular system appeared preferable to a work station or to adaptation of present designs. More work and the construction of prototypes are indicated if the anaesthetic machine is to be modern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(17 citation statements)
references
References 2 publications
3
13
0
Order By: Relevance
“…The results on variations in action density also fit very well with research on workload in anaesthesia (Gaba andLee 1990, Weinger et al 2004b). When focusing on the composition of anaesthetists' activity patterns during the different phases of anaesthesia, the results of this study are in line with previous task analysis studies in anaesthesia (Kennedy et al 1976, Boquet et al 1980, McDonald and Dzwonczyk 1988, Manser and Wehner 2002.…”
Section: Activity Patterns Over the Different Phases Of Anaesthesiasupporting
confidence: 88%
See 1 more Smart Citation
“…The results on variations in action density also fit very well with research on workload in anaesthesia (Gaba andLee 1990, Weinger et al 2004b). When focusing on the composition of anaesthetists' activity patterns during the different phases of anaesthesia, the results of this study are in line with previous task analysis studies in anaesthesia (Kennedy et al 1976, Boquet et al 1980, McDonald and Dzwonczyk 1988, Manser and Wehner 2002.…”
Section: Activity Patterns Over the Different Phases Of Anaesthesiasupporting
confidence: 88%
“…An approach based on (behavioural) task analysis is proposed as a first step to gain a better understanding of the similarities and differences between simulation environment and clinical work settings in anaesthesia. Task analysis methods have already been applied successfully in studies on human factors issues in the performance of anaesthesia in the clinical setting (Kennedy et al 1976, Boquet et al 1980, Weinger et al 1994, Weinger and Slagle 2002. In a previous field study using task analysis, the authors observed distinct variations in anaesthetist's activity patterns depending on the anaesthetic procedure, the phase of an anaesthetic procedure and the occurrence of non-routine events (Manser and Wehner 2002).…”
Section: Methodsmentioning
confidence: 99%
“…They discuss the effects of time-sharing; signal frequency, strength, and mode of presentation; noise; environmental pollution; and sleep deprivation. Probably the most comprehensive study to date that effectively uses these ergonomic techniques was published by Boquet et al [8]. They filmed the actions of anesthetists at work and measured, with an oculometer, where the anesthetists were looking at any instant.…”
mentioning
confidence: 99%
“…immobility and consciousness) (Xiao, 1994) in dynamic and complex environments with varying or high workload and risk levels (Gaba & Howard, 1995). It is for this reason that a vast amount of patient monitoring research has traditionally been focused on the anaesthesia environment (Boquet, Bushman, & Davenport, 1980;Loeb et al, 1989;Mylrea et al, 1993;Navabi et al, 1989;Seagull & Sanderson, 2001;Thompson, Watson, & Sanderson, 2005;Watson et al, 1999;Williams & Beatty, 2005) with more focuses on nursing staff (Potter et al, 2005) and home care being reviewed in recent times particular due to the developed world's increasingly aging population.…”
Section: Users Of the Patient Monitoring Equipmentmentioning
confidence: 99%
“…This is mainly due to the fact that medical staff, such as anaesthetists and nurses, do not consistently have their visual attention focused on the monitoring equipment; rather, their primary visual focus is on the patient, preparing charts, or drawing up medication. Weinger and Englund (1990) note that Boquet et al (1980) found, after analysing 16 hours of filmed anaesthetic activities, that 60% of the visual activity was directed at either the patient or the surgical field, with only 5% directed at the monitors.…”
Section: Types Of Auditory Displays Used In Medical Equipmentmentioning
confidence: 99%